Clinical Competencies for the Care of Hospitalized Patients with Alcohol Use Disorders. (22nd April 2020) - Phillips, Thomas; Porter, Amy; Sinclair, Julia
Abstract: Aims: The UK government aims to develop alcohol care teams (ACTs) that provide care for alcohol dependence in general hospital settings. Service descriptors have been identified to support the development of ACTs. The aim of this study was to use Delphi panel principles to identify the clinical competencies required to provide these elements of service. Methods: We formed an expert consensus panel of 24 senior clinical alcohol practitioners, leaders and experts by experience drawn from all regions of England. The study was divided into three distinct phases: (a) a review and synthesis of current literature in this area, (b) a face-to-face meeting of the expert panel and (c) subsequent iterations to refine the competencies until consensus was reached. Results: Our initial search strategy resulted in 555 competency statements being extracted from a range of national clinical professional and occupational standards and other sources. The research team refined these statements to 98 competencies in advance of the expert meeting. The panel identified 14 additional statements and reduced the number of competencies to 78. Subsequent iterations finalized 72 competencies across the 8 service descriptors. Conclusions: Drawing on the existing published resources and clinical experience, the expert panel has provided consensus on the core clinical competencies required for alcohol care teams in caring for hospitalized patients with alcohol use disorders. Whilst it is acknowledged that the range of current provision is variable, these competencies provide a template for clinical practice and the development of multidisciplinary ACTs.